Analisis Faktor-Faktor yang Mempengaruhi Audit Delay - Jayanti Sukining Tiyas, 08.05.52.0057; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2012)
This study aims to test empirically the. effect of firm size, profit / loss, auditor reputation, and profitability of the audit delay in manufacturing companies listed on the Indonesia Stock Exchange. This study uses secondary data, namely the financial statements of 135 companies listed on the Indonesia Stock Exchange as many as 82 companies to be sampled in 2008-2010. To prove the hypothesis, the test begins the classic assumption.The results of hypothesistesting with multiple regression found empirical evidence that the variable profitability and significant negative effect on audit delay. As for the variables of firm size, profit / loss, and the auditors reputation has no effect on audit delay.Keywords: audit delay, firm size, profit / loss, auditor reputation, and profitability